2022
DOI: 10.32996/jcsts.2022.4.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Saudi Arabia Individuals' Attitudes toward Electronic Personal Health Records

Abstract: This study is one of the few studies that examined the perspectives and expectations of Saudi Ariba patients regarding ePHRs. Participants expressed a greater interest in ePHRs than participants in other studies in developed countries. The majority of participants would like to use ePHRs at least once per month. Moreover, respondents believe that ePHRs help access images and blood test results, and information about the devices they use to track their health. For example, the blood glucose checkers. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The strategy covers the National Transformation Program, among which are eight themes of enhancing healthcare services quality and efficiency through a patientcentred healthcare culture and enhanced patient involvement using technology [138]. With the introduction of eHealth to the Kingdom of Saudi Arabia healthcare, researchers have initiated research into its different aspects [39,51,[139][140][141][142][143][144][145][146][147]. Most studies have examined the influencing factors on intention towards PHR use at the pre-adoption stage, while a few focused on the influencing factors at the usage stage.…”
Section: Research Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategy covers the National Transformation Program, among which are eight themes of enhancing healthcare services quality and efficiency through a patientcentred healthcare culture and enhanced patient involvement using technology [138]. With the introduction of eHealth to the Kingdom of Saudi Arabia healthcare, researchers have initiated research into its different aspects [39,51,[139][140][141][142][143][144][145][146][147]. Most studies have examined the influencing factors on intention towards PHR use at the pre-adoption stage, while a few focused on the influencing factors at the usage stage.…”
Section: Research Contextmentioning
confidence: 99%
“…Similarly, Saudi Arabian patients' perspectives and expectations were tackled by Alhur [51] in his study of PHR, which found participants to be highly interested in the system compared to other studies in developed nations. Most were inclined towards PHR use, perceiving them as valuable to health, albeit some expressed security concerns regarding online records.…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing clear, transparent governance that documents and reviews AI-supported decisions is essential to maintaining trust and ensuring AI serves as an aid to human decision-makers, not a replacement. These accountability measures reinforce the role of healthcare professionals in interpreting AI suggestions within the broader context of patient care [ 33 - 36 ].…”
Section: Reviewmentioning
confidence: 87%
“…Technology is being integrated into a variety of aspects of Saudi society in ways that were not prevalent in the past [60,[60][61][62][63][64][65][66][67][68]. As a result of the significance of HIT in the age of digitalization, a variety of stakeholders in Saudi Arabia are interested in investigating, integrating, evaluating, and implementing it.…”
Section: Discussionmentioning
confidence: 99%